F-AFLP GENOME SCAN AMONG FOURTEEN GENOTYPES OF SUNFLOWER (Helianthus annuus L.) - M. Rizk; F. Abd El-Twab; A. Abo Doma; M. Amar; M. Magdy (Arab Universities Journal of Agricultural Sciences, 2018)
Sunflower (Helianthus annuus L.) belongs to the family Asteraceae. The current study used the fluorescent amplified fragment length polymorphism (F-AFLP) technique for evaluating the genetic diversity among 14 sunflower genotypes including eight agronomical traits. Highly significant difference between genotypes was observed for all studied traits (p≤ 0.01). The results of correlation between the studied traits (p≤ 0.05) revealed that positive correlations were observed between most of the traits. Six F-AFLP combination were succeeded in the development of 178 molecular markers within a total of 1007 polymorphic bands, with 97.42% polymorphic percentage. Concerning the molecular markers associated traits, 73 were observed related to morphological and yield component traits. These results may facilitate the simultaneous selection of several economic traits and can thus improve the efficacy of selection based on F-AFLP in the sunflower breeding programs.